Development of Hydrogel with Anti-Inflammatory Properties Permissive for the Growth of Human Adipose Mesenchymal Stem Cells. (30th March 2016) - Sánchez-Sánchez, R.; Martínez-Arredondo, E.; Martínez-López, V.; Melgarejo-Ramírez, Y.; Brena-Molina, A.; Lugo-Martínez, H.; Gómez-García, R.; Garciadiego-Cázares, D.; Silva-Bermúdez, P.; Márquez-Gutiérrez, E.; Ibarra, C.; Velasquillo, C.
Abstract : Skin wound repair requires the development of different kinds of biomaterials that must be capable of restoring the damaged tissue. Type I collagen and chitosan have been widely used to develop scaffolds for skin engineering because of their cell-related signaling properties such as proliferation, migration, and survival. Collagen is the major component of the skin extracellular matrix (ECM), while chitosan mimics the structure of the native polysaccharides and glycosaminoglycans in the ECM. Chitosan and its derivatives are also widely used as drug delivery vehicles since they are biodegradable and noncytotoxic. Regulation of the inflammatory response is crucial for wound healing and tissue regeneration processes; and, consequently, the development of biomaterials such as hydrogels with anti-inflammatory properties is very important and permissive for the growth of cells. In the last years, it has been shown that mesenchymal stem cells have clinical importance in the treatment of different pathologies, for example, skin injuries. In this paper, we describe the anti-inflammatory activity of collagen type 1/chitosan/dexamethasone hydrogel, which is permissive for the culture of human adipose-derived mesenchymal stem cells (hADMSC). Our results show that hADMSC cultured in the hydrogel are viable, proliferate, and secrete the anti-inflammatory cytokine interleukin-10 (IL-10) but not the inflammatory cytokine Tumor Necrosis Factor-alpha (TNF- α ).